2017
DOI: 10.1007/s10584-017-2067-0
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of climate engineering: a focus group study of lay publics in four countries

Abstract: This study explores sense-making about climate engineering among lay focus group participants in Japan, New Zealand, the USA and Sweden. In total, 23 qualitative focus group interviews of 136 participants were conducted. The analyses considered sense-making strategies and heuristics among the focus group participants and identified commonalities and variations in the data, exploring participants' initial and spontaneous reactions to climate engineering and to several recurrent arguments that feature in scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…Perhaps more importantly, respondents did not mention geoengineering strategies in their assessments of actions the government could take to slow or stop global warming (open‐ended responses), and when directly asked about geoengineering (closed‐ended responses) they rated it as unfamiliar, extremely difficult, and less effective than other actions. These findings help contextualize the public antipathy toward geoengineering found in focus groups in the United States and other countries (e.g., Wibeck et al., ). By implication, this also suggests that people do not perceive anthropogenic greenhouse gas emissions as intentional, or as geoengineering, despite the fact that they effectively constitute uncontrolled geoengineering on a massive scale.…”
Section: Discussionmentioning
confidence: 71%
“…Perhaps more importantly, respondents did not mention geoengineering strategies in their assessments of actions the government could take to slow or stop global warming (open‐ended responses), and when directly asked about geoengineering (closed‐ended responses) they rated it as unfamiliar, extremely difficult, and less effective than other actions. These findings help contextualize the public antipathy toward geoengineering found in focus groups in the United States and other countries (e.g., Wibeck et al., ). By implication, this also suggests that people do not perceive anthropogenic greenhouse gas emissions as intentional, or as geoengineering, despite the fact that they effectively constitute uncontrolled geoengineering on a massive scale.…”
Section: Discussionmentioning
confidence: 71%
“…A common critique of geoengineering is that unlike mitigation it merely treats the symptoms of climate change rather than reducing the cause (i.e., high concentrations of atmospheric GHGs) (Anshelm and Hansson, 2014;ETC Group Heinrich Böll Foundation, 2017;Wibeck et al, 2017). However, GGR draws GHGs out of the atmosphere after they are emitted, thus raising the question of whether it treats the symptoms or the cause.…”
Section: Social Ethical and Political Concerns Treating The Symptoms?mentioning
confidence: 99%
“…Some of these inequalities in participation (and indeed outcomes) might be countered by engaging directly with communities and groups not normally regarded as having relevant ideas or perspectives, thereby shedding light on “civic epistemologies” of geoengineering (Jasanoff, ). Carr and Yung (), for example, have sought to explore public perceptions of geoengineering in a range of non‐Western contexts (including sub‐Saharan Africa and the South Pacific), while others have engaged with citizens in diverse settings in the global North, including in Finnish Lapland (Buck, ), Haida Gwaii (Gannon & Hulme, ), Japan (Asayama et al., ), New Zealand, Sweden and the USA (Wibeck et al., ). Geographers have much to contribute to these emerging strands of enquiry, drawing not just on the tools of ecofeminist critique, political ecology and environmental justice, but also on unique disciplinary approaches to the concept of place itself.…”
Section: New Geographies Of Geoengineering: Inequality the Productiomentioning
confidence: 99%
“…Several of those geoengineering experiments which have taken place have attracted a great degree of public interest and controversy (see, for example, Stilgoe, 2015), andwith more experiments plannedthis is likely to intensify. While some studies across nation states have shown that public perceptions of geoengineering can be similar (Carr & Yung, 2018;Wibeck et al, 2017), a growing body of research is illuminating the importance of situated knowledge (Hulme, 2008), contextual framings (Bellamy et al, 2012), deliberative spaces (Bellamy et al, 2017), particular places (Buck, 2018a) and local meanings (Gannon & Hulme, 2018) in shaping perceptions of the various technologies. Geographical context is also crucial, moreover, to the form and substance of emerging guidelines and incentives for responsible geoengineering research and development in different contexts (Bellamy, 2018;Buck, 2018b).…”
Section: Introduction: Geoengineering and Geographical Thoughtmentioning
confidence: 99%